Inhibitors in nonsevere haemophilia A: outcome and eradication strategies - van Velzen, Alice S.; Eckhardt, Corien L.; Hart, Daniel P.; Peters, Marjolein; Rangarajan, Savita; Mancuso, Maria Elisa; Smiers, Frans J.; Khair, Kate; Petrini, Pia; Jimenez-Yuste, Victor; Hay, Charles R. M.; van der Bom, Johanna G.; Yee, Thynn T.; Fijnvandraat, Karin; for the INSIGHT study group (Thrombosis and Haemostasis, 2015)
In nonsevere haemophilia A (HA) patients the presence of an inhibitor may exacerbate the bleeding phenotype dramatically. There are very limited data on the optimal therapeutic approach to eradicate inhibitors in these patients. We aimed to describe inhibitor eradication treatment in a large cohort of unselected nonsevere HA patients with inhibitors. We included 101 inhibitor patients from a source population of 2,709 nonsevere HA patients (factor VIII 2–40 IU/dl), treated in Europe and Australia (median age 37 years, interquartile range (IQR) 15–60; median peak titre 7 BU/ml, IQR 2–30). In the majority of the patients (71 %; 72/101) the inhibitor disappeared; either spontaneously (70 %, 51/73) or after eradication treatment (75 %, 21/28). Eradication treatment strategies varied widely, including both immune tolerance induction and immunosuppression. Sustained success (no inhibitor after rechallenge with factor VIII concentrate after inhibitor disappearance) was achieved in 64 % (30/47) of those patients rechallenged with FVIII concentrate. In high-titre inhibitor patients sustained success was associated with eradication treatment (unadjusted relative risk 2.3, 95 % confidence interval 1.3–4.3), compared to no eradication treatment. In conclusion, in nonsevere HA patients most inhibitors disappear spontaneously. However, in 35 % (25/72) of these patients an anamnestic response still can occur when rechallenged, thus disappearance in these patients does not always equal sustained response. Treatment for those requiring eradication has to be decided case by case, as one single approach is unlikely to be appropriate for all.Study was carried out in: Emma Children’s Hospital, Academic Medical Center, Amsterdam, the Netherlands.
Keywords: Haemophilia A; factor VIII inhibitors; eradication treatment; immune tolerance induction